Parent's General and Specific Attitudes and Children's Test Anxiety - Latifoglu, Gozde; Uzunboylu, Huseyin; Kagan, Sertan (Kamla-Raj Enterprises, 2017)
The aim of this study is to investigate randomly selected students' parents' general and specific attitudes regarding their children and students' test anxiety according to their gender, age, number of siblings and nationality during an examination period. A total of 668 females and 334 males from 7th and 8th grades form the population of this study. The results showed no significant differences between males and females on the Parental Attitude Scale and Parental Attitudes Scale Specific to Examination Period scores. However, the researchers found that there is a significant difference between the gender variable and Test Anxiety Emotionality subscale scores. The researchers concluded that female students had higher emotionality subscale scores compared to male students. Significant differences between different age groups and Test Anxiety worry and emotionality subscale scores have been found. Finally, there are significant differences between parental attitudes and the number of siblings and nationality variables
Keywords: Anxiety; Education; Exam; Parents; Students